Translating the Arabidopsis thaliana Peroxisome Proteome Insights to Solanum lycopersicum: Consensus Versus Diversity - Tarafdar, Sabiha; Chowdhary, Gopal (Frontiers in Cell and Developmental Biology, 2022)
Peroxisomes are small, single membrane specialized organelles present in all eukaryotic organisms. The peroxisome is one of the nodal centers of reactive oxygen species homeostasis in plants, which are generated in a high amount due to various stress conditions. Over the past decade, there has been extensive study on peroxisomal proteins and their signaling pathways in the model plant Arabidopsis thaliana and a lot has been deciphered. However, not much impetus has been given to studying the peroxisome proteome of economically important crops. Owing to the significance of peroxisomes in the physiology of plants during normal and stress conditions, understating its proteome is of much importance. Hence, in this paper, we have made a snapshot of putative peroxisomal matrix proteins in the economically important vegetable crop, tomato (Solanum lycopersicum, (L.) family Solanaceae). First, a reference peroxisomal matrix proteome map was generated for Arabidopsis thaliana using the available proteomic and localization studies, and proteins were categorized into various groups as per their annotations. This was used to create the putative peroxisomal matrix proteome map for S. lycopersicum. The putative peroxisome proteome in S. lycopersicum retains the basic framework: the bulk of proteins had peroxisomal targeting signal (PTS) type 1, a minor group had a PTS2 while the catalase family retained its characteristic internal PTS. Apart from these, a considerable number of S. lycopersicum orthologs did not contain any “obvious” PTS. The number of PTS2 isoforms was found to be reduced in S. lycopersicum. We further investigated the PTS1s in the case of both the plant species and generated a pattern for canonical and non-canonical PTS1s. The number of canonical PTS1 proteins was comparatively lesser in S. lycopersicum. The non-canonical PTS1s were found to be comparable in both the plant species however, S. lycopersicum showed greater diversity in the composition of the signal tripeptide. Finally, we have tried to address the lacunas and probable strategies to fill those gaps.